PENGARUH CAR, BOPO, NPF DAN FDR TERHADAP ROA BANK SYARIAH PERIODE 2010 -2015 - Yosi Stefhani (Jurnal Manajemen, 2016)
The purpose of this study is to figure out the influence of CAR, BOPO, NPF and FDR on ROA Islamic Bank period 2010-2015. The population in this study are all Islamic Bank in Indonesia. Sampling technique used is purposive sampling. The sample in this study there are 11 Islamic Bank period 2010 to 2015. The data analysis method used is multiple regression analysis. The results showed that only BOPO has effect to ROA Islamic Bank. Three other variables CAR, NPF and FDR did not aff'ect the ROA Islamic Bank. The other result shown simultaneously CAR, ROA, NPF and FDR effect on ROA Islamic Bank.